Reforming the legislation on the circulation of civilian weapons in Ukraine as a promising direction for combating organized crime - Klymenko, S.V.; Kamensky, D.V. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The research paper is devoted to the analysis of the prospects for regulatory regulation of the circulation of civilian firearms in Ukraine, in particular in the context of finding ways to combat organized crime. The authors consider the problem of uncontrolled proliferation of weapons associated with the ongoing war, and analyze legislative initiatives, primarily the draft Law No. 5708 “On the Right to Civilian Firearms”. They emphasize the need for a balance between the right of citizens to self-defense and the prevention of criminalization of society, drawing attention to the experience of other countries (USA, Switzerland, Czech Republic), where the legalization of weapons in society is accompanied by strict control. Special attention has been paid to the analysis of Ukraine’s international obligations, in particular, the implementation of the requirements of the UN Protocol against the Illicit Traffic in Firearms, which is an addition to the UN Convention against Transnational Organized Crime. Special emphasis is placed on the need to create a unified state system of weapons registration and strengthen international cooperation in this area. The authors offer specific recommendations for improving the regulatory framework that will allow Ukraine to more effectively counter the threats associated with the illegal spread of firearms, while ensuring the legitimate rights of citizens to necessary defense. The research offers arguments for and against the legalization of weapons, including potential risks such as increased violence, corruption in the licensing system, and the use of weapons by criminal groups. The authors propose a comprehensive approach to regulation that would combine liberalization with increased accountability and the creation of effective accounting and control mechanisms. The conclusions of the work emphasize the need for legislative reform taking into account international standards and domestic challenges related to the safety of citizens and crime prevention. The authors justify the need to create transparent accounting mechanisms, strengthen control, and simultaneously liberalize the legislation, which will allow citizens to exercise their constitutional right to self-defense without threatening public safety. It was concluded that the development of the regulatory framework in this area should be balanced and meet both domestic challenges and international standards for combating organized crime.